2018
DOI: 10.1097/hjh.0000000000001584
|View full text |Cite
|
Sign up to set email alerts
|

Phase II randomized sham-controlled study of renal denervation for individuals with uncontrolled hypertension – WAVE IV

Abstract: Our data did not prove that antihypertensive efficacy of the externally delivered focused ultrasound for RDN was greater than the sham effect. Stabilization of BP at baseline was identified as an important determinant of BP changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Reasons for the failure of external ultrasound RDN to provide a significant reduction in BP over and above sham therapy have been previously described 17. It would be reasonable to propose that this novel technology actually did not achieve renal denervation based upon the BP response alone, but 2 lines of evidence support the hypothesis that renal nerve ablation did occur following active therapy in our study.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Reasons for the failure of external ultrasound RDN to provide a significant reduction in BP over and above sham therapy have been previously described 17. It would be reasonable to propose that this novel technology actually did not achieve renal denervation based upon the BP response alone, but 2 lines of evidence support the hypothesis that renal nerve ablation did occur following active therapy in our study.…”
Section: Discussionsupporting
confidence: 70%
“…This study is a single‐center substudy of the Wave IV Study: Phase II Randomized Sham Controlled Study of Renal Denervation for Subjects With Uncontrolled Hypertension study, an international, multicenter, randomized, sham‐controlled, double‐blind clinical trial of RDN in subjects with treatment‐resistant hypertension 17. The study had approval from a Central Research Ethics Committee and all participants gave written informed consent to take part in the main study and the substudy.…”
Section: Methodsmentioning
confidence: 99%
“…However, HIFU requires good quality images to visualise the target, which may be difficult in overweight patients. Although initial clinical evaluation using HIFU reported effectiveness in office BP reduction, the recently published randomised sham-controlled WAVE IV study showed no difference in office or 24-hour ambulatory BP reduction between the RAD and the sham control arms at 24 weeks [48,52].…”
Section: Ultrasound (Us)mentioning
confidence: 95%
“…The decreases in systolic pressure in the denervation (n = 364) compared with the control (n = 171) group were 14.1 mmHg vs. 11.7 mmHg and 6.8 mmHg vs. 4.8 mmHg on office and ambulatory monitoring, respectively, resulting in baseline-adjusted intergroup differences of 2.4 mmHg (95% CI 2.1-6.9 mmHg; p = 0.26) and 2.0 mmHg (95% CI -1.0-5.0 mmHg; p = 0.98) [60]. SYMPLICTY HTN-3 [60] and other trials reporting similarly disappointing [37,[61][62][63][64][65][66] or borderline significant [67] results, even if all of them confirmed the safety of the procedure, shattered the prospect of bringing renal denervation to clinical application in treatment-resistant hypertension (Fig. 2).…”
Section: Device-based Treatmentmentioning
confidence: 98%
“…2), only WAVE IV (NCT02029885) [66] applied externally delivered ultrasound energy to sever the renal nerves. All other trials [37,38,[58][59][60][61][62][63][64][65][66] used an intraarterial approach to deliver radiofrequency energy. A randomised trial using intravascularly delivered ultrasound energy is ongoing (RADIANCE-HTN; NCT02649426) and expected to report in 2018.…”
Section: Device-based Treatmentmentioning
confidence: 99%